Antenatal diagnosis of Niemann-Pick disease in a twin pregnancy. Issue 5 (October 1981) - Donnai, P; Donnai, D; Harris, R; Stephens, R; Young, E; Campbell, S
Abstract : An Ashkenazi Jewish woman had a child with Niemann-Pick disease in her first marriage. She subsequently remarried a man who was also heterozygous for the condition and conceived twins. Prenatal diagnostic tests were performed and one twin was shown to be homozygous and the other heterozygous for Niemann-Pick disease. The problems of prenatal diagnosis and counselling in twin pregnancies are discussed.